Initiating the Javanese Methodology: Discourse, Characteristic, and Paradigm - Sahid Teguh Widodo; Septi Yulisetiani; Suyatno Suyatno (Javanologi: International Journal of Javanese Studies, 2023)
Java is a cultural center that is quite influential in the Southeast Asian Region. Since centuries ago, Java has always been the center of attention of products of high cultural knowledge and knowledge. The specific purpose of this research is to develop at an early stage the Java methodology. This research is very strategic to do because the data shows that research on the subject of Javanese culture always shows results that are not optimal. On the other hand, the use of Western methodologies is not able to reach the core Javanese values so that Java only be seen from the outer structure. This study seeks to compile the initial stages of the formulation of the Javanese methodology by collecting data from various Javanese sources, including from the informant, written sources, textbooks, Javanese ancient manuscripts, and various existing traditional ceremonies. The results show that (1) Java has a different conception of truth that has an impact on its methodological implications, (2) the Javanese methodology has a different paradigm, (3) the Javanese methodology is authentic in the attitudes, behavior, and ways of the Javanese people in carrying out their cultural life.Keywords: Methodology; Java; research; culture.